Strategies for Schools Management to Protect and Help Students in the Situation of the Coronavirus Disease 2019 (COVID-19) Epidemic, in Schools under the Buriram Primary Educational Service Area Office - Innok, Niphon; Phanichanurak, Rattima (Academic MCU Buriram Journal, 2023)
The purpose of this research were: 1) to create strategies for school management 2) to protect and help students in the situation of the coronavirus disease 2019 (COVID-19) epidemic of schools in Buriram Primary Educational Service Area Office. The research is divided into 4 phases. Phase 1: study of the need for school management 3) to protect and help students by brainstorming a total of 18 people and a study of administrative needs from school administrators of 201 people. Phase 2: creating a strategy for school management to protect and help students by 5 experts. Phase 3: the trial of the school management strategy 4) to protect and help students by assessing the level of practice of 201 educational institutions, developing strategies by seminars based on 9 experts. Phase 4: strategic evaluation of educational institutions management to protect and assist students in the epidemic situation of the Corona virus Disease 2019 (COVID-19). The research results found that: 1. Educational institution administrators have a need to manage educational institutions to protect and help students in the situation of the epidemic of corona virus disease 2019 (COVID-19), the overall picture is at the highest level. 2. Strategies for school management to protect and help students in the situation of the corona virus disease 2019 (COVID-19) epidemic, Buriram Primary Educational Service Area Office. There are 5 main strategies: 1) Participatory management. 2) Building safety for students. 3) Arrangement of learning activities in accordance with the situation. 4) Protection of students. 5) Follow-up of children back to school. There are 19 Sub-strategies and 78 items. 3. The results of the strategy experiment found that 1) 201 educational institutions Implement school management strategies to protect and assist students in epidemic situations of the coronavirus disease 2019 (COVID-19) and is at the highest level in all strategies. 2) Messages in the low performance list have been improved, and 14 other items that experts consider to be defective. 4. Strategic assessment results showed that 1) educational institute administrators, teachers, basic education committees and students are satisfied with the school management strategy to protect and help students in the situation of the epidemic of coronavirus disease 2019 (COVID-19), the Buriram Office of Primary Education Area is at the highest level. 2) 32,141 students are safe from the coronavirus 2019 infection, representing a percentage of 99.76%. 3) The school followed 172 students back into the education system, representing a percentage of 98.28. 3) The quality of life of students in the coronavirus disease 2019 (COVID-19) outbreak situation is high.